Learning by making: A framework to revisit practices in a constructionist learning environment - Morado, María Florencia (2021)
Makerspaces are collaborative workspaces where people construct their ideas using a variety of ma terials and tools ranging from no tech to high tech, where components can be moulded and transformed into different projects depending on each maker’s vi sion. Educational makerspaces allow educators to respond to the diverse interests of individual learners. This paper documents the learning of participants at an educational makerspace founded on construction ist principles. We analyse the characteristics of the Maker Movement and the features of an educational makerspace, identify learning dimensions, select a case, analyse field notes, photos and videos using an interpretivist paradigm and refine the practical framework guiding the facilitation of the case study discussed. Given that the investigators are also the facilitators of the activities, this framework allows an a posteriori analysis of the practices used to make learning visible.